2017
DOI: 10.1213/ane.0000000000002027
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Clinical Trial on the Effects of a Valveless Trocar on Respiratory Mechanics During Robotic Radical Cystectomy: A Pilot Study

Abstract: During RARC, use of a VT was associated with a significantly lower Pplat and improvement in other respiratory parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…On the other hand, it is unclear how the AirSeal ® played a role in the positive responses because we did not compare the data from a conventional insufflation system. However, two studies [ 2 , 21 ] demonstrated that CO 2 elimination was significantly reduced with the AirSeal ® versus conventional insufflation system. CO 2 elimination rates are reportedly directly related to CO 2 absorption rates when the patient remains metabolically constant [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is unclear how the AirSeal ® played a role in the positive responses because we did not compare the data from a conventional insufflation system. However, two studies [ 2 , 21 ] demonstrated that CO 2 elimination was significantly reduced with the AirSeal ® versus conventional insufflation system. CO 2 elimination rates are reportedly directly related to CO 2 absorption rates when the patient remains metabolically constant [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minute ventilation has to be increased by up to 15% to match the respiratory demand generated by increased CO 2 resorption in pneumoperitoneum [25]. The use of a valve-less trocar by the surgeons has been shown to improve respiratory mechanics in robot-assisted radical cystectomy and could help to ease ventilatory demands if prolonged pneumoperitoneum is required [26]. If ventilatory adjustment is not possible, the surgeons should be asked to reduce IAP or stop the CO 2 flow for a few minutes.…”
Section: Co 2 Resorptionmentioning
confidence: 99%
“…Furthermore, CO2 use is demonstrated to be significantly decreased using such a system, resulting in a potential reduction in CO2-related complications; this is of particular benefit for patients with impaired cardiopulmonary function [ 11 ]. In randomized experiments in urology, the system improved visualization and reduced cardiopulmonary damage compared to standard insufflation [ 12 , 13 , 14 ]. The AirSeal platform has been evaluated in general gynecologic surgery, mainly in cases of benign disease [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%